Why do More Open Economies Have Bigger Governments? - Rodrik, Dani (Journal of Political Economy, 1998)
There exists a positive correlation between an economy's exposure to international trade and the size of its government. The correlation holds for most measures of government spending, in low- as well as high-income samples, and is robust to the inclusion of a wide range of controls. One explanation is that government spending plays a risk-reducing role in economies exposed to a significant amount of external risk. The paper provides a range of evidence consistent with this hypothesis. In particular, the relationship between openness and government size is strongest when terms-of-trade risk is highest.